Selective covalent targeting of SARS-CoV-2 main protease by enantiopure chlorofluoroacetamide - Yamane, Daiki; Onitsuka, Satsuki; Re, Suyong; Isogai, Hikaru; Hamada, Rui; Hiramoto, Tadanari; Kawanishi, Eiji; Mizuguchi, Kenji; Shindo, Naoya; Ojida, Akio (Chemical science (Cambridge), 2022)
The coronavirus disease 2019 (COVID-19) pandemic has necessitated the development of antiviral agents against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The main protease (M pro ) is a promising target for COVID-19 treatment. Here, we report an irreversible SARS-CoV-2 M pro inhibitor possessing chlorofluoroacetamide (CFA) as a warhead for the covalent modification of M pro . Ugi multicomponent reaction using chlorofluoroacetic acid enabled the rapid synthesis of dipeptidic CFA derivatives that identified 18 as a potent inhibitor of SARS-CoV-2 M pro . Among the four stereoisomers, ( R , R )-18 exhibited a markedly higher inhibitory activity against M pro than the other isomers. Reaction kinetics and computational docking studies suggest that the R configuration of the CFA warhead is crucial for the rapid covalent inhibition of M pro . Our findings highlight the prominent influence of the CFA chirality on the covalent modification of proteinous cysteines and provide the basis for improving the potency and selectivity of CFA-based covalent inhibitors.